TINJAUAN YURIDIS PERANAN BANK, KEPOLISIAN DAN PPATK DALAM MENCEGAH DAN MEMBERANTAS TINDAK PIDANA PENCUCIAN UANG - Josep '; Erdianto '; Syaifullah Yophi A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Money laundering is a criminal act which arise with the development of advanced science and technology, well as utilizing the the financial system includes banking system to conceal or obscure the origins of the proceeds from of money laundering. Money laundering is a huge loss impact so it requires inter-agency cooperation to prevent and eradicate it. Bank, Police, and INTRAC has essential role in preventing and combating money laundering.The purpose of writing this essay to discuss several issues that is how the role of the Bank, Police, and INTRAC in Preventing and Combating money laundering, how the INTRAC relations with other law enforcement institutions as well as the constraints faced by the Bank, Police, and INTRAC in preventing and combating criminal acts of money laundering and also the efforts by the Bank, Police, and INTRAC in overcoming those constraints. This research is a normative study with qualitative descriptive characteristicsThe results of this study is the role of the Bank, Police, and INTRAC is essential in the prevention and combating of money laundering and the three parties needs to perform their duties and functions in order to prevention and combat money laundering goes well, INTRAC need additional authority which an investigations authority in order to use INTRAC Analysis results can be used as evidence to start an investigation of money laundering crimes act ,in their roles has few constraints which must be solved by them.The authors suggested enhance the synergy between the parties that contribute in preventing and combating money laundering, revision of Law No. 8 of 2010, the implementation of a single identity number, and the improvement of the quality of each of the parties that contribute in the prevention and combating money launderingKeywords: Money Laundering -Role- Bank - Police- INTRAC